Increased CCL-5 (RANTES) Gene Expression in the Choroid Plexus of Dogs with Canine Leishmaniosis - Silva, José Eduardo dos Santos [UNESP]; Jussiani, Giulia Gonçalves [UNESP]; Grano, Fernanda Grecco [UNESP]; Pelissari, Maria Cecília Clarindo [UNESP]; de Melo, Guilherme Dias; Negrão Watanabe, Tatiane Terumi; de Lima, Valéria Felix [UNESP]; Machado, Gisele Fabrino [UNESP] (MDPI, 2023)
Visceral canine leishmaniasis (CanL) can cause several clinical manifestations, including neurological lesions. Few reports have characterized the lesions observed in the central nervous system (CNS) during CanL; however, its pathogenesis remains unclear. The choroid plexus (CP) is a specialized structure responsible for the production and secretion of cerebrospinal fluid (CSF) and considered an interface between the peripheral immune system and CNS. It can allow the passage of inflammatory cells or pathogens and has the potential to act as a source of inflammatory mediators in several diseases. Thus, this study aimed to evaluate the role of CP as a possible route of inflammatory cells in the development of brain lesions in dogs with CanL, as well as its association with blood–CSF barrier (BCSFB) dysfunction. Samples were collected from 19 dogs that were naturally infected with CanL. We evaluated the histopathological lesions in the brain and investigated the gene expression of the cytokines. Capture enzyme-linked immunosorbent assay (ELISA) was used to evaluate the presence of the same cytokines in the CSF. Biochemical analysis was performed to compare the presence of albumin in the serum and CSF. Indirect ELISA was performed to measure the presence of anti-Leishmania antibodies in the CSF, which would suggest the disruption of the BCSFB. Histopathological evaluation of the dogs’ brains revealed mild-to-severe inflammatory infiltrates, mainly in the CP and meninges. We also detected the presence of anti-Leishmania antibodies and albumin in the CSF, as well as Leishmania DNA in the CP. The gene expression of CCL-5 was increased in the CP of infected dogs compared with that of controls, and there was a tendency for the increase in the gene expression of CXCL-10. Thus, our findings confirm the disfunction of the BCSFB during CanL and suggest that the chemokines CCL-5 and CXCL-10 can be responsible for the recruitment of inflammatory cells found in CP.
Keywords: central nervous system; cerebrospinal fluid; chemokines; neuroinflammation